Faktor - Faktor yang berhubungan dengan Preeklampsia pada Ibu Hamil Trimester III - Andira; Sri Rahayu (Politeknik Baubau, 2023)
Preeclampsia is hypertension that occurs in pregnant women at 20 weeks of gestation or after delivery which is marked by an increase in blood pressure to 140/90 mmHg. The aim of this research is determine the factors associated with preeclampsia in third trimester pregnant women in the dahlia room at the Public Hospital. Sample: The sample of this study were third trimester pregnant women with preeclampsia as many 124 people.This type of research uses quantitative analytic methods with a cross-sectional approach. Results: there is a significant relationship between preeclampsia, gestational age, parity, history of hypertension and family history of pregnant women with the results of the chi-square test statistical test obtained p-value <0.05.